Robot-assisted radical prostatectomy in the Middle East: A report on the perioperative outcomes from a tertiary care centre in Lebanon. Issue 2 (3rd April 2021) - Labban, Muhieddine; Bulbul, Muhammad; Wazzan, Wassim; Khauli, Raja; El Hajj, Albert
ABSTRACT: Objective: To report on the surgical, oncological and early functional outcomes of robot-assisted radical prostatectomy (RARP) at our tertiary care centre, as there is a scarcity of reports on outcomes of robotic surgery from the Middle East. Patients and methods: We reviewed the electronic health records for patients undergoing RARP between 2013 and 2019 at the American University of Beirut Medical Center. We collected patients' demographics and preoperative oncological factors including prostate-specific antigen (PSA), clinical oncological stage, and World Health Organization (WHO) grade. PSA persistence, biochemical recurrence (BCR) and positive surgical margin (PSM) were reported. Complications were categorised by Clavien–Dindo grade. Moreover, the postoperative oncological outcomes including the rates of adjuvant and salvage androgen-deprivation therapy (ADT) and external-beam radiation therapy (EBRT), chemotherapy, and metastasis were reported. Additionally continence and potency results were retrieved. Results: For the designated period, 250 patients underwent RARP of which 182 (72.8%) underwent lymph node dissection. The median (interquartile range) anaesthesia time was 330 (285–371) min and the estimated blood loss was 200 (200–300) mL. The overall complication rate was 8%, with 2% Clavien–Dindo Grade III–IV complications. The PSM and BCR rates were 21.6% and 6.4%, respectively. Adjuvant ADT and EBRT was administered to 7.2% of the patients. Functional data was available for 112 patients. Continence was 68%, 82% and 97% of the patients at 3, 6 and 12 months, respectively. For 65 patients who had bilateral nerve sparing potency was 37%, 60% and 83% at 3, 6 and 12 months, respectively. Conclusion: This is the largest RARP series from the Middle East. The surgical, oncological and functional outcomes are consistent with those published in the literature. This confirms the safety and efficacy of applying robotic technology in our region during the implementation phase. Abbreviations: ADT: androgen-deprivation therapy; AJCC: American Joint Committee on Cancer; AUBMC: American University of Beirut Medical Center; BCR: biochemical recurrence; CPT: Current Procedural Terminology; EBRT external beam radiation therapy; IQR, interquartile ranges; LOS: length of stay; PLND: pelvic lymph node dissection; PSM: positive surgical margin; (O)(RA)RP, (open) (robot-assisted) radical prostatectomy